Generation of linearly polarised light near in a cascaded, random distributed feedback Raman laser. (December 2016) - Zlobina, E.A.; Kablukov, S.I.; Babin, S.A.
Abstract: We have demonstrated efficient generation of linearly polarised light by a random distributed feedback laser based on stimulated Raman scattering in a -long fibre, pumped by linearly polarised radiation of an ytterbium-doped fibre laser with a lasing wavelength near . Cascaded generation up to the fifth Stokes component with wavelength tuning by changing the pump wavelength is obtained. The output power of the fourth Stokes component reached at . The problems related to the further mastering of the long-wavelength region are discussed.